Tracking and the intergenerational transmission of education: Evidence from a natural experiment - Marten von Werder; Simon Lange (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Proponents of tracking argue that the creation of more homogeneous classes increases effciency while opponents point out that tracking aggravates initial differences between students. We estimate the effects on the intergenerational transmission of education of a reform that delayed tracking by two years in one of Germany's federal states. While the reform had no effect on educational outcomes on average, it increased educational attainment among individuals with uneducated parents and decreased attainment among individuals with educated parents. The effect is driven entirely by changes in the gradient for males and to a large extent by an effect on the likelihood to complete the academic secondary track.
Keywords: I21; I24; I28; J62; 330; tracking; educational institutions; educational inequality; equality of opportunity; intergenerational mobility